Design of central composite of zinc removal from model water using chitosan biopolymer - Qudsieh, Isam Y.; Mirghani, Mohamed Elwathig Saeed; Kabbashi, Nassereldeen Ahmed; Muyibi, Suleyman Aremu (AENSI Publications, 2014)
This research project intended to study the performance of chitosan as flocculating agent for removal heavy metal (zinc) from artificial water. Chitosan was used due to its special characteristics such as non-toxic, hydrophilic, biodegradable, biocompatible, and anti-bacterial, biopolymer and very good adsorption of heavy metal which has led to a very diverse range of its applications. The presence of a large number of amine groups on the chitosan chain increases it adsorption capacity. The effect of contact time, dosage of chitosan, agitation speed and pH were observed for optimal absorption of the zinc in synthetic water. Thus, the application of conventional jar test method used for removal of zinc from synthetic water. Thus, the results of this project which is 52.40% of percentage removal of zinc with optimum conditions; pH7, 30mg dosage, 12 minutes of contact time, and 190 rpm agitation speed approved that chitosan competent to be the alternative adsorbent.